Sustainable Urban Planning Policies & their role in Achieving Spatial Equity A Case Study: City of Damascus - Niveen Riad al-Zebaq (Tishreen University, 2019)
يُعدُّ التخطيط الحضري المستدام من الموضوعات الحديثة والمعاصرة، ولكنَّ أساليب وطرائق العمل بها ماتزال غير واضحة المعالم بشكلٍ كافٍ، ولاسيّما دورها في تحقيق المساواة المكانية والارتقاء بالمناطق المهمشة، لذلك انطلق البحث من تأسيس قاعدة نظرية من خلال تعريف مفهومي التخطيط الحضري المستدام والمساواة المكانية والعلاقة بينهما، والتوصّل إلى أهمّ المؤشّرات التي تقيس المساواة المكانية. ثم دراسة وتحليل التجربة التنموية للبرازيل ومدينة برشلونة للوصول إلى أهم سياسات التخطيط الحضري المستدام التي استطاعت تحقيق التكامل بين السياسات الاقتصادية والاجتماعية والبيئية والعمرانية من أجل تحقيق تنمية متوازنة مستدامة، ثم قام البحث بدراسة وتحليل الواقع الراهن لمدينة دمشق وريفها الملاصق ورصد أهمّ المؤشّرات التنموية فيهما وصولاً إلى أهمّ التوجّهات التنموية والسياسات التخطيطية التي يجب اتّباعها لتنمية المدينة والإرتقاء بالمناطق المهمّشة فيها، وتحسين مستوى معيشة الأفراد وصولاً إلى تحقيق مساواة مكانية. Sustainable urban planning is one of modern and contemporary themes, but the techniques and methods of working out are still unclear enough, especially its role in achieving spatial equity and the advancement of neglected areas.   The research started from the definition of the concepts of sustainable urban planning and spatial equity and the relationship between them, then reaches to the most important indicators that measure spatial equity. It Studies and analyzes the developmental experience of Brazil and the city of Barcelona to reach the most important sustainable urban planning policies that have been able to achieve integration between the economic, social, environmental and urban policies in order to achieve balanced sustainable development. Then the research studies and analyzes the current reality of the city of Damascus and its adjacent countryside, and monitors the most important development indicators in them. Then it comes to the most important development trends and policy planning that must be followed for the development of the city and improving its neglected areas, to improve the standard of living then achieve spatial equity.